(untitled) (Theatrum historiae, 2013)
The study introduces the basic outline of conceptions and characteristics of historical approaches to origin of illness and contagion. Essential were primarily the decomposition of ancient Hippocratic-Galen paradigm and the birth of a new model of consideration and defining of illness in the period between the Renaissance and the mid-19th century. We focus on three issues: the question of the definition of illness; efforts to create “nosological” classification schemes; efforts to understand the disease contagion, and the transmission and spread of disease.